Pengaruh Pelayanan Administrasi Akademik Terhadap Kepuasan Taruna/I Politeknik Bumi Akpelni Semarang - Iik Suryati Azizah; Tini Utami (Universitas 17 Agustus 1945 Semarang, 2024)
In improving the quality and satisfaction of cadets,each Politeknik Bumi Akpelni must bi serious about paying attention to the needs and axpectations of the cadets and correcting all existing deficiencies. This improving academic administration service and administrative staff services. Politeknik Bumi Akpelni must be able to accept suggetions and constructive criticism internal parties, especially from cadets. From this background the problem that arises is : providing services regarding the level of satisfaction of cadets ad Politeknik Bumi Akpelni Semarang. The aim is to find out The level of satisfacation with academic services towards the level of satisfaction of cadet at Politeknik Bumi Akpelni Semarang.Based on the problem, the reserch method used is descriptive verification.The research results show that the services provided by academics are very important, the performance of the services provided to cadets ad Politeknik Bumi Akpelni Semarang can meet the expectations of cadets. Thus, academics must pay attention to and respond to complaints submitted by cadets ad Politeknik Bumi Akpelni Semarang. The Academi is expected to regularly is expected training and development to employees who directly deal with student.